Half a chance - Lord, Cynthia (Scholastic Press, 2014)
Lucy, with her mother and her photographer father, has just moved to a small rural community in New Hampshire, and with her new friend Nate she plans to spend the summer taking photos for a contest, but pictures sometimes reveal more than people are willing to see.